Bruton’s tyrosine kinase: an emerging targeted therapy in myeloid cells within the tumor microenvironment - Good, Logan (Cancer Immunol Immunother, 2021)
Bruton’s tyrosine kinase (BTK) is a non-receptor kinase belonging to the Tec family of kinases. The role of BTK in B cell receptor signaling is well defined and is known to play a key role in the proliferation and survival of malignant B cells. Moreover, BTK has been found to be expressed in cells of the myeloid lineage. BTK has been shown to contribute to a variety of cellular pathways in myeloid cells including signaling in the NLRP3 inflammasome, receptor activation of nuclear factor-κβ and inflammation, chemokine receptor activation affecting migration, and phagocytosis. Myeloid cells are crucial components of the tumor microenvironment and suppressive myeloid cells contribute to cancer progression, highlighting a potential role for BTK inhibition in the treatment of malignancy. The increased interest in BTK inhibition in cancer has resulted in many preclinical studies that are testing the efficacy of using single-agent BTK inhibitors. Moreover, the ability of tumor cells to develop resistance to single-agent checkpoint inhibitors has resulted in clinical studies utilizing BTK inhibitors in combination with these agents to improve clinical responses. Furthermore, BTK regulates the immune response in microbial and viral infections through B cells and myeloid cells such as monocytes and macrophages. In this review, we describe the role that BTK plays in supporting suppressive myeloid cells, including myeloid-derived suppressor cells (MDSC) and tumor-associated macrophages (TAM), while also discussing the anticancer effects of BTK inhibition and briefly describe the role of BTK signaling and BTK inhibition in microbial and viral infections.